2015
DOI: 10.4401/ag-6637
|View full text |Cite
|
Sign up to set email alerts
|

Passive degassing at Nyiragongo (D.R. Congo) and Etna (Italy) volcanoes

Abstract: <p>Volcanoes are well known as an impressive large natural source of trace elements into the troposphere. Etna (Italy) and Nyiragongo (D.R. Congo) are two stratovolcanoes located in different geological settings, both characterized by persistent passive degassing from their summit craters. Here, we present some results on trace element composition in volcanic plume emissions, atmospheric bulk deposition (rainwater) and their uptake by the surrounding vegetation, with the aim to compare and identify diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…Compared to subalkalic basaltic volcanic gas plumes, only a small number of alkaline volcanic gas plumes have been sampled directly for their source metal emissions: at Mt. Erebus, Antarctica (Wardell et al, 2008), and Nyiragongo, Democratic Republic of the Congo (Calabrese et al, 2014). Alkaline intraplate magmas are typically chlorine-rich, which may produce higher concentrations of gaseous volatile metals than subalkalic basaltic intraplate volcanoes due to the higher availability of chloride ligands in the exsolved fluids (Mandon et al, 2019), although this has not yet been demonstrated.…”
Section: Volcanism In the West Antarctic Rift Systemmentioning
confidence: 99%
“…Compared to subalkalic basaltic volcanic gas plumes, only a small number of alkaline volcanic gas plumes have been sampled directly for their source metal emissions: at Mt. Erebus, Antarctica (Wardell et al, 2008), and Nyiragongo, Democratic Republic of the Congo (Calabrese et al, 2014). Alkaline intraplate magmas are typically chlorine-rich, which may produce higher concentrations of gaseous volatile metals than subalkalic basaltic intraplate volcanoes due to the higher availability of chloride ligands in the exsolved fluids (Mandon et al, 2019), although this has not yet been demonstrated.…”
Section: Volcanism In the West Antarctic Rift Systemmentioning
confidence: 99%